The environmental disclosures of the electricity generation industry: a global perspective - Alrazi B.; de Villiers C.; Van Staden C.J. (Routledge, 2023)
The electricity generation industry has been under close regulatory and public scrutiny for decades for the significant impacts its activities have on the environment. The industry is responsible for a large proportion of greenhouse gas (GHG) emissions, which has intensified public and regulatory scrutiny of late. Therefore, electricity generation firms face immense pressure to show environmental responsibility. Firms respond with environmental disclosures in their annual reports, in stand-alone-reports, and on websites. In this study, we use comprehensive disclosure indices to measure the quality (or comprehensiveness) of the CO2 emissions related disclosure and the overall environmental disclosure of 205 electricity generation firms in 35 countries. We find that firms in countries with a high commitment towards the environment and a carbon emissions trading scheme (measures of social concern for environmental protection and emissions), are likely to disclose more comprehensive environmental information. In addition, we find that firm size, age of the assets, listing status, and media exposure influence disclosure. Environmental performance, measured by CO2 emissions, is not significantly related to environmental disclosure among our sample firms. The theoretical implication of these findings is that social beliefs (that are different in different countries) prompt a legitimating disclosure response from firms that is not significantly affected by their performance against that social belief. 2016 Informa UK Limited, trading as Taylor & Francis Group.